2015
DOI: 10.1200/jco.2014.60.2334
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Cohort Study of Hospital Palliative Care Teams for Inpatients With Advanced Cancer: Earlier Consultation Is Associated With Larger Cost-Saving Effect

Abstract: A B S T R A C T PurposePrevious studies report that early palliative care is associated with clinical benefits, but there is limited evidence on economic impact. This article addresses the research question: Does timing of palliative care have an impact on its effect on cost? Patients and MethodsUsing a prospective, observational design, clinical and cost data were collected for adult patients with an advanced cancer diagnosis admitted to five US hospitals from 2007 to 2011. The sample for economic evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
209
2
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 227 publications
(227 citation statements)
references
References 33 publications
8
209
2
8
Order By: Relevance
“…Nonetheless, there is compelling evidence that early involvement of palliative care services improves quality of life, patient satisfaction, care giver satisfaction and in some settings can improve overall survival [51][52][53]. Incorporating palliative care into cancer care, particularly early in the patient journey may also offer the possibility of substantial cost-savings [51,54]. Thus, increasing access to palliative care for patients with blood cancers, including those pursuing disease-directed treatment, may offer huge opportunities to improve care while also reducing health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there is compelling evidence that early involvement of palliative care services improves quality of life, patient satisfaction, care giver satisfaction and in some settings can improve overall survival [51][52][53]. Incorporating palliative care into cancer care, particularly early in the patient journey may also offer the possibility of substantial cost-savings [51,54]. Thus, increasing access to palliative care for patients with blood cancers, including those pursuing disease-directed treatment, may offer huge opportunities to improve care while also reducing health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized studies of palliative care interventions have shown improved quality of life and greater patient satisfaction, while potentially reducing costs through reductions in aggressive treatment strategies [55,56]. As such, the increased use of palliative care within ACOs would potentially improve VBC while incorporating patient-centered values [57,58].…”
Section: Innovative Models Of Carementioning
confidence: 99%
“…20 Bundled payment reimbursement could increase the use of palliative care because of its demonstrated cost savings. [7][8][9][10][11][12][13][14] CMS and private insurers should also explore reimbursing providers for telehealth consultations, which could facilitate access to specialty-level palliative care in programs that do not have physicians and in rural and other safetynet settings. 32,33 Health system managers have a responsibility to ensure that palliative care is available and of high quality.…”
Section: Discussionmentioning
confidence: 99%
“…1,6 Growth in palliative care programs has been driven in part by evidence that palliative care improves patient outcomes and satisfaction, while reducing costs associated with intensive medical care. 1,[7][8][9][10][11][12][13][14] Palliative care can be provided in settings throughout the continuum of care, but the predominant model in the United States (outside of hospice care) is the hospital consultative team model. 3 Central to this model are interprofessional teams, which can include physicians, advanced practice and other registered nurses, social workers, chaplains, pharmacists, rehabilitation therapists, direct care workers, and other clinical and nonclinical specialists.…”
mentioning
confidence: 99%